Dengue and Chikungunya Co-infection Evolving into Systemic Lupus Erythematosus – Case Report - Wahinuddin Sulaiman; Dev Teo Cin Nee; Zakaria Abdul Kadir; Ahmad Helmi Abdul Karim; Chun Lai Too (Asian Journal of Medicine & Health Sciences, 2022)
Viral infections are a common triggering factor in the initiation of autoimmune diseases. Dengue and chikungunya infections have been reported independently in the literature as triggering factors for patients who are predisposed to autoimmune diseases such as SLE. We report a 19-year-old girl who presented with dengue and chikungunya co-infection, subsequently manifested florid signs and serological markers of active SLE complicated by pneumonitis, hepatitis, and upper gastrointestinal hemorrhage. The co-infection of dengue and chikungunya fever was confirmed by positive test to dengue and chikungunya immunoglobulin M (IgM). Both dengue and chikungunya infections exhibit distinct clinical phenotypes but share a common mechanism of disrupting the immune system and triggering immune complex formation which predispose to the development of autoimmune diseases such as SLE. This was the first case we encountered where arboviruses co-infection evolved into SLE. It is important to learn from this complex case especially in our region where both dengue and chikungunya infections are endemic, considering the unfavorable outcome if improperly addressed and managed.